2020
DOI: 10.1016/j.matlet.2019.127116
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous electrospun cellulose acetate butyrate nanofibres for oil sorption

Abstract: Porous superhydrophobic nanofibrous networks based on cellulose acetate butyrate (CAB) were prepared using electrospinning. The morphology and wettability of the prepared fibrous networks was studied using scanning electron microscopy and static contact angle measurements. The porous nanofiber networks exhibited superhydrophobicity and superoleophilicity with a water contact angle of ~165° and an oil contact angle of ~0°. The porous nature of the nanofibres themselves is thought to lead to an increased surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Additionally, it is inherently hydrophobic because of its butyryl chains (Huang et al 2018). Recently, Tanvir et al (2020) produced superhydrophobic electrospun CAB fibers that exhibited four times higher oil adsorbent capacity (60 g/g) than commercial polypropylene. The authors also reported that the surface porosity of CAB fibers considerably increased the oil sorption capacity, with the hydrophobicity of the porous fibers being superior than that of non-porous CAB fibers.…”
Section: Cellulose Acetate Butyratementioning
confidence: 99%
“…Additionally, it is inherently hydrophobic because of its butyryl chains (Huang et al 2018). Recently, Tanvir et al (2020) produced superhydrophobic electrospun CAB fibers that exhibited four times higher oil adsorbent capacity (60 g/g) than commercial polypropylene. The authors also reported that the surface porosity of CAB fibers considerably increased the oil sorption capacity, with the hydrophobicity of the porous fibers being superior than that of non-porous CAB fibers.…”
Section: Cellulose Acetate Butyratementioning
confidence: 99%
“…Due to the superoleophilicity of the porous structure, CAB absorbed all the oil within 60 s and remained afloat on the surface of the water, allowing for easy retrieval (Figure 8F). [200]…”
Section: Natural Bio-sorbentmentioning
confidence: 99%
“…The suspensions were vibrated at 180 rpm for 12 h at 298 K. After that, the composite was collected by ltrations. To determine the adsorbed Ce 4+ , the residue Ce 4+ concentration was measured by CPA-MA according to the previous report [1,2], and the adsorbed Ce 4+ can be calculated by the difference between the original and the residue concentrations. Naked eyes and a solid-state visible spectrophotometer were used to qualitatively and quantitatively investigate the color change of the hybrid after Ce 4+ loading.…”
Section: Measurement and Removal Of Ce 4+mentioning
confidence: 99%
“…However, most of them require expensive instruments and skilled operators, and usually are hard to be used on site. As to the removal of REE in water, sorption is one of the most widely applied techniques because of its cheapness and facile operation [1].…”
Section: Introductionmentioning
confidence: 99%